Спектральний метод граничних інтегральних рівнянь в фотоніці - Ілляшенко, Л. М.; Стогній, Н. П.; Нерух, О. Г. (ХНУРЕ, 2019)
Modern developments of nanophotonic mechanisms are presented. The set of numerical experiments illustrates performances of algorithms, made with spectral boundary integral equation method, allowing to solve a lot of new challenging problems. With novel algorithms the dependence of resonating wavelength on various parameters, including shape, size, material properties and coupling induced properties of nanodetails, such as interparticle distance, orientation and position of the light source in novel configurations may be found.
Keywords: Спектральний метод; фотоніка; інтегральні рівняння